Whole genome sequencing of Neisseria gonorrhoeae reveals transmission clusters involving patients of mixed HIV-serostatus - Peters, J; Cresswell, F; Amor, L; Cole, K; Dean, G; Didelot, X; De Silva, D; Eyre, D; Paul, J (BMJ Publishing Group, 2017)
Objectives Prevention and control of gonorrhoea depends on understanding the nature of sexual networks and risk factors for infection.  We aimed to use high resolution typing (whole genome sequencing) of Neisseria gonorrhoeae isolates plus patient questionnaire data to gain insights into transmission patterns in a high prevalence setting. Methods During a nine month period (July 2014-March 2015) patients diagnosed with gonorrhoea attending sexual health service in Brighton, UK, were invited to provide anonymised detailed information by questionnaire about risk factors for infection.  Questionnaire data plus whole genome sequence data from cultured isolates were analysed to yield information about sexual networks and risk factors for infection.   Results 104/149 individuals who consented to participate in the study were culture-positive. 97/104 (93%) were male.  80 self-reported to be men who have sex with men (MSM).  35/104 (34%) of patients were HIV-positive. 51/104 (49%) individuals reported using geosocial networking applications to facilitate contact.  Sex under the influence of drugs was reported by 16/34 (46%) of HIV-positive MSM, 17/41 (41%) of HIV-negative MSM and 5/15 (31%) of heterosexuals.  WGS data were available for 100 isolates from 83 patients.  55 isolates (66%) belonged to genetically related subtypes involving one or more patients, who could be plausibly linked through recent direct or indirect transmission.  Four transmission clusters containing 3-12 individuals were composed of MSM of mixed HIV-serostatus. Conclusions We show that data obtained from whole genome sequencing of Neisseria gonorrhoeae and enhanced epidemiological data obtained from patient questionnaires are mutually supportive and reveal insights into sexual networks.  Our findings suggest that serosorting may have declined as a practice and indicate the importance of designing public health interventions that target infection risks associated with recreational drug use and contact made using geosocial networking applications.